A pictured Africa: drawing as a visual qualitative research methodology for examining British African Diaspora imaginings of their ancestral 'home'. Issue 4 (8th August 2022) - Ademolu, Edward
Abstract : This article examines the usefulness of participant-produced drawings as a participatory and non-mechanical visual research methodology in qualitative research with UK-based African Diaspora communities. Because of its co-construction and mediation of situated knowledgies, adaptability and with linguistic proficiency a non-prerequisite skill for drawing literacy; participatory drawings are considered particularly productive and ethically sound for work with children, young people and in the case of this research, adults, in different social and cultural contexts. Thematic and critical discourse analyses of drawings, supplemented by textual/written information and subsequent discussions about these visual productions, have the powerful potential to unearth complex (and seemingly hidden) subtleties of thought, memories, sentiments and information for (and by) participants, in ways that are illustrative, self-empowering, and individualised. As a review of drawing methodology, as a visual qualitative research method, the author discusses its usefulness and limitations, using his work with African Diaspora communities for/as context.